Paraneoplastic Syndromes Associated with Ovarian Teratomas - Systematic Review - Kulczykowska , Wiktoria; Krzyśkowska, Sylwia; Kozińska, Anna; Krukowska, Kamila; Krupa, Martyna; Krawiec, Laura (Quality in Sport, 2026)
Ovarian teratomas are germ cell tumors characterized by their ability to differentiate into tissues derived from all three embryonic germ layers. Although most teratomas are benign, particularly mature cystic teratomas, they may be associated with a wide spectrum of paraneoplastic syndromes. These syndromes are not caused by the direct presence of the tumor but rather by immune-mediated or hormonal mechanisms triggered by the neoplasm. The most well-recognized association is anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis, although other neurological, hematological, and systemic manifestations have also been described. This systematic review aims to analyze the types of paraneoplastic syndromes associated with ovarian teratomas, their pathophysiology, clinical presentation, and diagnostic significance. Particular attention is given to neurological autoimmune syndromes, which often precede tumor diagnosis and may serve as an early clinical indicator of an underlying neoplasm. Understanding these associations is essential for timely diagnosis and appropriate management, which frequently involves a combination of tumor resection and immunotherapy.